Morph_CNeT: A new GIS tool to extract morphometric attributes characterising channel network topology of Indian catchments - Saroj Rana; Sagar Rohidas Chavan (Journal of Hydrology: Regional Studies, 2025)
Study region: 21 River Basins comprising 1749 Catchments within India. Study focus: The morphometric attributes related to the channel network topology of a catchments are derived as functions of the emergence of the 1st, 2nd and 3rd bifurcation nodes of the network. These attributes are found to have influence on the shape of width function and hydrologic responses from catchments. There is a dearth of attempts to utilize these attributes in hydro-geomorphological applications, may be due to the complexity involved in their extraction owing to lack of any algorithmic procedure. This study is envisaged to develop an easy-to-use and time efficient Python based GIS code/tool named as Morph_CNeT within ArcGIS framework which provides an algorithmic way to extract the morphometric attributes. New hydrological insights for the region: Morph_CNeT is utilized to derive topological attributes for 1749 hydrological observation sites belonging to 21 river basins within India to build a repository titled “Morph_CNeT-India”. Subsequently, the attributes are used to classify the catchments into several types of network topology as a function of the relative positions of first 3 internal nodes as well as their distances from the outlets. Finally, the empirical width functions constructed based on the morphometric attributes are shown to capture the multi-peaked behaviour of hydrographs to highlight significance of the attributes. The repository of morphometric attributes can form the basis for carrying out several hydro-geomorphological investigations.